Development Model for Increasing Community Participation in Tourism Management of Open Pit Nam Salu Geosite in East Belitung Regency - Qurayma, Vinki Adindani; Raya, Alia Bihrajihant; Fatonah, Siti; Witjaksono, Roso; Wahyudin, Nanang (Agro Ekonomi, 2024)
Tourism sector plays an important role in increasing the country's foreign exchange and promoting the creation of jobs to improve the economy. In this context, community organizations manage tourism sites, and the leaders are tasked with directing members to achieve common objectives. An important tourist site is Open Pit Nam Salu Geosite and participation is relatively low since people depend on illegal tin mining. Village government and community organizations are less assertive in overcoming the problems. Therefore, this research aims to analyze development model for increasing participation in tourism management of Open Pit Nam Salu Geosite in Senyubuk Village, Kelapa Kampit District. The location determination was carried out purposively, with 87 respondents selected by cluster sampling method through the PLS test. The results showed an indirect effect of community capital and leadership on participation through group roles. Meanwhile, leadership promoted participation since community capital and group roles served as mediator variables. Pokdarwis and village government were also strengthened in organizing community to maximize the potential of capital in the region and mobilize BAPOPNAS group to manage tourism daily.